A pair of new chiral polyoxovanadates with decent NLO properties. Issue 17 (16th April 2018) - Cao, Jiapeng; Xiong, Yao; Luo, Ximing; Chen, Lu; Shi, Jie; Zhou, Mengjie; Xu, Yan
Abstract : Through utilizing a two-step method to successfully prepare a pair of enantiomers trataric-polyoxovanadate [(l /d -C4 O6 H2 )2 V4 O8 ]·2C6 N2 H18 (1-L or1-D ), these compounds show decent third-order NLO property and electrochemical behavior. Abstract : Two pure enantiomers of polyoxovanadate clusters [(l -/d -C4 O6 H2 )2 V4 O8 ]·2C6 N2 H18 (abbreviated as1-L and1-D ) have been synthesized by a two-step method. During the two-step synthesis process, we first carried out the solvothermal synthesis and then evaporated the solvent, ending up with orange-yellow crystals. The unique chiral architectures are built up by a single chiral ligand (tartaric acid) and polyoxovanadium. The chiralities of the products were confirmed by circular dichroism (CD) spectra. Due to the presence of protonated free tetramethyl ethylenediamine (TMEDA) cations, the adjacent clusters and TMEDA cations can be connected by hydrogen-bonding interactions. The V4 cluster linked adjacent clusters via hydrogen bonds to form a 3D supramolecular network. The open aperture Z -scan spectra of two compounds show that molecular TPA cross-section σ of1-L and1-D are 1412 and 1094 GM, respectively, which illustrate that they feature decent third-order NLO properties and may have great potential applications as NLO materials.